Patient-reported experience of clinical care of osteogenesis imperfecta (OI) during the COVID-19 pandemic - Smyth, Debra; Hytiris, Monica; Kelday, Coreen; McDonnell, Ciara; Burren, Christine; Gardner, Adrian; Mills, Lisa; Parekh, Susan; Semler, Oliver; Stewart, Angela; Westerheim, Ingunn; Javaid, Muhammad Kassim; et al. (Frontiers in Public Health, 2023)
Background Research on the effects of the COVID-19 pandemic on people with rare diseases is limited. Few studies compare healthcare throughout the progression of the ongoing pandemic. Aims To assess the impact of the pandemic on individuals with osteogenesis imperfecta across two consecutive years, understand what challenges were encountered, and analyse the experience of remote consultation. Methods An initial survey was distributed following the first lockdown in August 2020, and a second survey in April 2021. The surveys explored four themes- effects on therapy, alternatives to consultation, effect on mental health, and perceived risks of COVID-19. Results In the 2020 survey, of the 110 respondents, 69 (63%) had at least one appointment delayed due to the lockdown, compared with 89 of the 124 respondents (72%) in 2021. Of the 110 respondents in 2020, 57 (52%) had a remote consultation, increasing to 92 of 124 (74%) in the follow-up survey. In the 2020 survey 63 of 91 respondents (69%) expressed anxiety due to lockdown, compared with 76 of 124 (61%) in 2021. The percentage of total respondents expressing a preference for remote consultation was 48% in 2020, increasing to 71% in 2021. Conclusions The pandemic has had widespread effects on the mental and physical health of those with OI. These effects, alongside appointment delays, have increased as the pandemic progresses. Encouragingly, the increasing preference for remote consultation may indicate that this could be a viable long-lasting alternative to face-to-face appointments, especially for patients who previously travelled vast distances for specialist care.